PENYULUHAN PENGOLAHAN SAMPAH RUMAH TANGGA SECARA DARING MELALUI METODE TAKAKURA OLEH KELOMPOK WANITA TANI KEBUN SAUYUNAN - Tita Rosita; Euis Mintarsih (IKIP SILIWANGI, 2021)
This activity aims to increase knowledge, skills, and public awareness about the processing of household waste. The large pile of household waste is caused by low public concern for waste. Therefore the solution must be related to the changing mindset of the community about waste. People need to know the types of waste that can be recycled, mostly garbage coming from households. Waste processing to produce useful products and have economic value is one way to change people's mindset that waste is something valuable. Mothers who are members of the Sauyunan Garden Farmer Group located in RW 03 Sarijadi Subdistrict Sukasari Bandung become the priority of implementing this socialization because as a pilot in the management of urban farming, that has been successful. However, the fertilizer/compost is still buying from outside. Processing of household waste to be used as fertilizer/compost is made using the takakura method of implementation is carried out utilizing counseling on the types of household waste, demonstrations on composting, and the practice of managing household waste